Polystichum recavum (subg. Haplopolystichum; Dryopteridaceae), a new cave fern from Guangxi, China - Wei, Hong-Jin; Zhang, Li-Bing (Phytotaxa, 2018)
A new species of Polystichum (subg. Haplopolystichum; Dryopteridaceae), P. recavum, is described from a limestone cave from southern Guangxi, China. Polystichum recavum is most similar to P. cavernicola in having oblanceolate lamina and oblong pinnae, but distinguishable from the latter in number of sterile pinna pairs, shape of pinna apex, and shape of the auricles.